The TERENO Pre‐Alpine Observatory: Integrating Meteorological, Hydrological, and Biogeochemical Measurements and Modeling. Issue 1 (1st November 2018) - Kiese, R.; Fersch, B.; Baessler, C.; Brosy, C.; Butterbach-Bahl, K.; Chwala, C.; Dannenmann, M.; Fu, J.; Gasche, R.; Grote, R.; Jahn, C.; Klatt, J.; et al.
Abstract : Core Ideas: Pre‐alpine areas face more intense warming and extreme hydrological events than the global average. Climate and land management change have far‐reaching impacts on ecosystem functions and services. We have improved knowledge of water, energy, and matter exchange by long‐term observations and modeling. Global change has triggered several transformations, such as alterations in climate, land productivity, water resources, and atmospheric chemistry, with far reaching impacts on ecosystem functions and services. Finding solutions to climate and land cover change‐driven impacts on our terrestrial environment is one of the most important scientific challenges of the 21st century, with far‐reaching interlinkages to the socio‐economy. The setup of the German Terrestrial Environmental Observatories (TERENO) Pre‐Alpine Observatory was motivated by the fact that mountain areas, such as the pre‐alpine region in southern Germany, have been exposed to more intense warming compared with the global average trend and to higher frequencies of extreme hydrological events, such as droughts and intense rainfall. Scientific research questions in the TERENO Pre‐Alpine Observatory focus on improved process understanding and closing of combined energy, water, C, and N cycles at site to regional scales. The main long‐term objectives of the TERENO Pre‐Alpine Observatory include the characterization and quantification of climate change and land cover–management effects on terrestrial hydrology and biogeochemical processes at site and regional scales by joint measuring and modeling approaches. Here we present a detailed climatic and biogeophysical characterization of the TERENO Pre‐Alpine Observatory and a summary of novel scientific findings from observations and projects. Finally, we reflect on future directions of climate impact research in this particularly vulnerable region of Germany.